2018
DOI: 10.1017/s1431927618000387
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Imaging of Zinc Soaps Nucleation in Oil Paint

Abstract: Using the recently developed techniques of electron tomography, we have explored the first stages of disfiguring formation of zinc soaps in modern oil paintings. The formation of complexes of zinc ions with fatty acids in paint layers is a major threat to the stability and appearance of many late 19th and early 20th century oil paintings. Moreover, the occurrence of zinc soaps in oil paintings leading to defects is disturbingly common, but the chemical reactions and migration mechanisms leading to large zinc s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…Based on these IR investigations it appears that the formation of zinc oxalates follows the formation of zinc soaps which recently has been shown to be present as ionomeric clusters [34][35][36][37][38]. We believe that these clusters could be the precursors for the formation of zinc oxalates by bond breaking and oxidation of the long chain fatty acids through a radical mechanism, the radicals possibly being caused by light absorption/photoactivity of ZnO.…”
Section: Ageing In 13 Co 2 Atmospherementioning
confidence: 82%
“…Based on these IR investigations it appears that the formation of zinc oxalates follows the formation of zinc soaps which recently has been shown to be present as ionomeric clusters [34][35][36][37][38]. We believe that these clusters could be the precursors for the formation of zinc oxalates by bond breaking and oxidation of the long chain fatty acids through a radical mechanism, the radicals possibly being caused by light absorption/photoactivity of ZnO.…”
Section: Ageing In 13 Co 2 Atmospherementioning
confidence: 82%
“…In support of this idea, transmission electron microscopy experiments have shown that zinc soap material formed in ZnO model paint is indeed very irregular, with crystalline domain sizes in the order of tens of nanometers. 12 Moreover, FT-IR spectra of zinc palmitate recrystallized from linseed oil have been reported that showed some signs of νa COO band splitting. 34…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the characterization of model paint samples prepared under controlled conditions with varying paint compositions (including different pigments, pigment‐to‐oil ratios and additives) allows the controlled study of the effect of paint ingredients on metal soap formation. [ 35 , 49 , 51 , 55 , 58 , 63 , 64 , 65 ]…”
Section: How To Detect Metal Soapsmentioning
confidence: 99%